Development of antibacterial coating on silicone surface via chlorhexidine-loaded nanospheres - Hathaichanok Phuengkham (2018)
© 2015, Springer Science+Business Media New York. Urinary tract infections (UTIs) are the most common type of hospital-acquired infection which cause significant morbidity and mortality. Antibacterial urinary devices to prevent UTIs are in great demand, while the problem of releasing antibacterials is still limited by duration of antibacterial release and hinders their clinical applications. This study investigated a new approach to sustain release of chlorhexidine (CHX) from urinary devices by coating of chlorhexidine-loaded nanospheres (CHX-NPs) on the surface. CHX-NPs were prepared by high-pressure emulsification-solvent evaporation technique that provided the size of nanospheres at 198.8 nm and the drug loading content at 5.6 %. These nanospheres were spray-coated on silicone surface with reproducible and predictable amount of CHX. Release studies conducted in artificial urine to mimic in vivo condition showed that suitable dose of CHX was released in a sustained manner within a couple of weeks. Additionally, CHX-NPs showed antibacterial activity against common bacteria causing UTIs up to 15 days, which is threefold longer than that of physical mixing between CHX and polymer. Results from this study suggest possible applications of CHX-NPs in coating the surface of ureteral-relating devices for sustained antibacterial release.